Method for rapidly evaluating printability of 3D printing concrete based on torque feedback

Through a rapid evaluation method based on torque feedback, the torque characteristics of concrete materials are measured using a small simulation unit, and the problem of time-consuming and labor-consuming evaluation of 3D printed concrete printability is solved, achieving rapid and accurate evaluation and printing parameter optimization.

CN119862682AActive Publication Date: 2025-04-22北京耐尔得智能科技有限公司

Patent Information

Application Number
CN202411695159.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-04-22
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The printability evaluation of 3D printed concrete is time-consuming and labor-intensive and wasteful, and the lack of a standardized and quantitative evaluation system, which makes it difficult to objectively compare the printability of different concrete ratios.

Method used

A rapid evaluation method based on torque feedback is adopted, and the torque characteristics of concrete materials are measured through a small simulation unit, the corresponding relationship between the torque-speed curve and the printing effect is established, the printability of concrete materials is judged and the printing parameters are optimized.

Benefits of technology

A rapid and quantitative concrete printability evaluation is achieved, which reduces material consumption in actual printing tests, improves evaluation efficiency and accuracy, and provides fast and accurate feedback for concrete material design and printing performance optimization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119862682A_ABST
    Figure CN119862682A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of 3D printing concrete, and particularly relates to a method for rapidly evaluating the printability of 3D printing concrete based on torque feedback, and the method comprises the steps: firstly setting an actual printing unit, a small simulation unit and an effect detection unit, and then enabling the actual printing unit and the small simulation unit to synchronously print and stir the same fresh concrete material; recording respective torque-rotating speed curves and printing effect evaluation, establishing a database in a one-to-one correspondence manner, obtaining a torque characteristic optimal printing interval according to existing data, then printing a concrete material with unknown characteristics through a small simulation unit, and judging whether the torque characteristic of the material falls into the torque characteristic optimal printing interval or not; the printability of the concrete material can be rapidly evaluated by using the method, the material consumption required by an actual printing test is reduced, and meanwhile, rapid and accurate feedback can be provided for concrete material design and printing performance targeted optimization; and the reliable evaluation of the printability of the material can be completed in only about 0.5 hour.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of 3D printing concrete, and in particular relates to a method for quickly evaluating the printability of 3D printing concrete based on torque feedback. Background Art

[0002] As an emerging construction method, 3D printing concrete technology has received widespread attention in recent years. The concrete materials used in 3D printing concrete technology require that the concrete has pumpability for smooth transportation through pipelines, extrudability for smooth extrusion through nozzles, stackability for smooth stacking after extrusion from nozzles, and volume stability for maintaining stability after stacking. These properties of concrete materials are mainly related to their rheological properties and setting time.

[0003] In 3D concrete printing operations, the printing parameters need to be matched according to the characteristics of the concrete material. However, the evaluation of the printability of concrete materials has always been one of the main challenges faced by this field. The rheological properties of the material directly determine the quality and efficiency of 3D printed concrete. The traditional 3D printing concrete evaluation method requires a large number of actual printing tests to determine the printing parameters of a certain concrete mix that has not been printed. This is not only time-consuming and labor-intensive, but also causes a large amount of material waste and high costs. In addition, due to the lack of a standardized and quantitative evaluation system, it is difficult to objectively compare the printability of different concrete mixes.

[0004] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for quickly evaluating the printability of 3D printed concrete based on torque feedback. The torque characteristics of the concrete material can be measured by a small simulation unit, and the printability of the concrete material can be quickly judged based on the results.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] A method for quickly evaluating the printability of 3D printed concrete based on torque feedback comprises the following steps:

[0008] Step S1: Equipment preparation and basic configuration:

[0009] An actual printing unit, a small simulation unit, and an effect detection unit are provided; the actual printing unit is a 3D printing device for carrying out actual 3D printing operations, and the stirring mechanism is built-in with a first sensor for real-time sensing and recording the torque generated by the motor during the stirring process of the 3D printing device; the small simulation unit has a stirring function and is built-in with a second sensor for recording the torque generated by the motor during the material stirring process; the effect detection unit is used to evaluate the printing result of the actual printing unit;

[0010] Step S2: Basic testing and data collection:

[0011] The actual printing unit and the small simulation unit simultaneously print and mix the same fresh concrete material, and record their respective torque-speed curves;

[0012] Step S3: Printing effect evaluation:

[0013] The standard test model is printed using the fresh concrete material, and the printing effect of the actual printing unit is scored using the effect detection unit; the corresponding relationship between the torque-speed curve and the printing effect of the actual printing unit and the small simulation unit is established;

[0014] Step S4: Establishing a database and determining optimal parameters:

[0015] Prepare concrete of various components, repeat steps S2 and S3, and construct a database of the torque-speed curve of the actual printing unit, the torque-speed curve of the small simulation unit, the printing effect, and the printing parameters of the actual printing unit;

[0016] Based on the numerical comparison of the printing effect results in the database, the optimal printing range of the torque characteristic is determined according to the optimal printing effect range; the torque characteristic includes the static torque growth rate and the dynamic torque growth rate;

[0017] Step S5: Printability evaluation of concrete material X:

[0018] For concrete material X with unknown printing characteristics, a small simulation unit is used to obtain the torque characteristics of concrete material X to determine whether the torque characteristics of the unknown concrete material fall within the optimal printing range of the torque characteristics; if it falls within the optimal printing range of the torque characteristics, the concrete material X has good printability and no proportion adjustment is required.

[0019] Furthermore, the method for quickly evaluating the printability of 3D printed concrete based on torque feedback also includes step S6, determining printing parameters: for concrete materials whose torque characteristics fall within the optimal printing range of torque characteristics, multiple groups of printing parameter tests are performed through an actual printing unit, and the optimal printing parameters are selected according to the result values ​​of the printing effect; the printing parameters include the travel rate of the travel mechanism and the extrusion rate of the stirring mechanism.

[0020] Furthermore, step S5 also includes a database updating step: entering the torque-speed curve, rheological parameters, printing effect score and optimal printing parameters obtained by testing the concrete material X with unknown printing characteristics into the database.

[0021] Furthermore, the comprehensive score E of the printing effect is:

[0022] E=50%×H+25%×S+25%×C,

[0023] in, In the formula, H is the height completion rate, H = h a / h0,h a is the actual printing height, h0 is the model preset height; F is the incidence of complete breakage of strips longer than 1 mm, N f is the number of layers where fracture occurs, N t is the total number of layers; V is the void distribution rate on the strip surface, A v is the gap area, A t is the total surface area; S is the strip surface integrity, C is the width excess rate, C0 is the number of measurement points where the width exceeds 120% of the preset width, and C t is the total number of measurement points;

[0024] The printing effect scoring result is 0-100%; when the score is ≥90%, it indicates that the material can be directly printed; when the score is <90%, it indicates that the material cannot be directly printed.

[0025] Furthermore, the optimal printing range of the torque characteristics is a static torque growth rate of 20-25 N·m / s and a dynamic torque growth rate of 15-20 N·m / (r / s).

[0026] Furthermore, the standard test model is a cylindrical model and a single-layer wall model. Single-layer wall model single layer 20×500mm 2 ; The actual printing unit travel speed is 60mm / s, the extrusion rate is 0.6r / s; the small simulation unit rotation speed is 0.6r / s.

[0027] Furthermore, based on the Bingham model, the static yield torque in the small simulation unit and the growth rate of the torque reflecting the elastic modulus with time are obtained by setting the low-speed constant shear mode; the dynamic yield torque and the growth rate of the torque reflecting the material viscosity with the rotational speed are obtained by setting the high-speed to low-speed shear mode; the correspondence between the torque-speed curve and the printing effect is obtained through consistent tests of different concrete materials and recorded in the database.

[0028] Furthermore, the small simulation unit is capable of performing rheological property tests based on the Bingham model; the shear force of the rheological property test procedure is applied using the small simulation unit to obtain the torque-time curve performance of the concrete material X corresponding to the unknown printing characteristics.

[0029] Further, the actual printing unit is a 3D printing device for carrying out actual 3D printing operations, and the actual printing unit includes a stirring mechanism and a traveling mechanism, wherein the stirring mechanism has the function of adjusting the nozzle traveling speed and the material extrusion speed during the printing process; the stirring mechanism is equipped with a first sensor for real-time sensing and recording the torque generated by the motor during the stirring process of the 3D printing device; the small simulation unit includes at least a second stirring mechanism, and the capacity of the second stirring mechanism is smaller than the capacity of the first stirring mechanism of the actual printing unit; the second stirring mechanism is equipped with a second sensor for real-time sensing and recording the torque and speed generated by the motor during the stirring process;

[0030] The effect detection unit is configured as a high-speed camera system with continuous recording and image recognition functions, which can continuously record the height of the 3D printed structure and the distribution and ratio characteristics of appearance defects when the actual printing unit is working; the effect detection unit has a built-in rapid analysis program system for evaluating the printing effect based on the height and completeness of the 3D printed structure.

[0031] Furthermore, the small simulation unit is a small stirring device or rheometer with a built-in torque-speed sensor.

[0032] The beneficial effects of the present invention are:

[0033] The purpose of the present invention is to provide a method for quickly evaluating the printability of 3D printed concrete based on torque feedback. The method aims to establish a rapid and quantitative concrete printability evaluation feedback system required for on-site printing, obtain the torque-speed curve of unknown concrete materials through miniaturized simulation equipment, thereby obtaining the torque characteristics, and then determine whether the torque characteristics fall into the optimal printing range of the torque characteristics, so as to quickly evaluate the printability of the concrete material, reduce the material consumption required for the actual printing test, and provide rapid and accurate feedback for the concrete material design and targeted optimization of printing performance;

[0034] The present invention uses a rapid evaluation method based on torque feedback to complete material printability evaluation and printing parameter optimization in only about 0.5 hours. Compared with traditional rheometer testing methods, the efficiency is greatly improved, and the evaluation results are consistent with the printing effect and reliable. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:

[0036] Figure 1 This is the dynamic shear result of the ZD-50 stirring device of the embodiment of the present invention.

[0037] Figure 2 This is the static shear result of the ZD-50 stirring device of the embodiment of the present invention.

[0038] Figure 3 Schematic diagram of printing of a standard test model of a cylinder according to an embodiment of the present invention.

[0039] Figure 4 It is a printing schematic diagram of a single-layer wall standard test model according to an embodiment of the present invention.

[0040] Figure 5 It is a schematic diagram of the static yield torque growth rate fitting of an embodiment of the present invention.

[0041] Figure 6 It is a schematic diagram of the dynamic yield torque growth rate fitting of an embodiment of the present invention.

[0042] Figure 7 It is a standard test model for comprehensively scoring different printing effects in the embodiments of the present invention.

[0043] Figure 8 This is the dynamic shear result of the rheometer according to the embodiment of the present invention.

[0044] Fig. 9 It is the static shear result of the rheometer of the embodiment of the present invention. DETAILED DESCRIPTION

[0045] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0046] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0047] A method for quickly evaluating the printability of 3D printed concrete based on torque feedback, characterized in that it comprises the following steps:

[0048] Step S1: Equipment preparation and basic configuration:

[0049] An actual printing unit, a small simulation unit, and an effect detection unit are provided; the actual printing unit is a 3D printing device for carrying out actual 3D printing operations, and the stirring mechanism is equipped with a first sensor for real-time sensing and recording the torque generated by the motor during the stirring process of the 3D printing device; the small simulation unit can quickly detect the rheological properties of the concrete material, and is equipped with a second sensor for recording the torque generated by the motor during the material stirring process; the effect detection unit is used to evaluate the printing result of the actual printing unit;

[0050] Step S2: Basic testing and data collection:

[0051] The actual printing unit and the small simulation unit simultaneously print and mix the same fresh concrete material, and record their respective torque-speed curves;

[0052] Step S3: Printing effect evaluation:

[0053] The standard test model is printed using the fresh concrete material, and the printing effect of the actual printing unit is scored using the effect detection unit; the corresponding relationship between the torque-speed curve and the printing effect of the actual printing unit and the small simulation unit is established; Figure 3 , Figure 4 The following is the standard test model printing status. Figure 7 A standard test model for comprehensively scoring different printing effects;

[0054] Step S4: Establishing a database and determining optimal parameters:

[0055] Prepare concrete of various components, repeat steps S2 and S3, and construct a database of torque-speed curves of the actual printing unit, torque-speed curves of the small simulation unit, rheological properties of concrete materials represented by torque-related parameters, printing effects, and printing parameters of the actual printing unit;

[0056] Based on the numerical comparison of the printing effect results in the database, the optimal printing range of the torque characteristic is determined according to the optimal printing effect range; the torque characteristic includes the static torque growth rate and the dynamic torque growth rate; according to the previous test results, the optimal printing range of the present invention is the static torque growth rate of 20-25N·m / s and the dynamic torque growth rate of 15-20N·m / (r / s);

[0057] The torque characteristics, rheological properties, etc. of the materials involved in the present invention are derived based on the Bingham model;

[0058] Step S5: Printability evaluation of concrete material X:

[0059] For concrete material X with unknown printing characteristics, a small simulation unit is used to obtain the torque characteristics of concrete material X, and to determine whether the torque characteristics of the unknown concrete material fall within the optimal printing range of the torque characteristics; if it falls within the optimal printing range of the torque characteristics, the concrete material X has good printability and no proportion adjustment is required; if not, the concrete material X cannot be directly printed and its formula needs to be optimized before evaluation;

[0060] At the same time, the torque-speed curve, torque-time curve, rheological parameters, printing effect score and optimal printing parameters obtained by testing the concrete material X with unknown printing characteristics are entered into the database to update the database;

[0061] Step S6: Determine printing parameters:

[0062] For concrete materials whose torque characteristics fall within the optimal printing range of torque characteristics, multiple groups of printing parameter tests are performed through an actual printing unit, and the optimal printing parameters are selected based on the result values ​​of the printing effect; the printing parameters include the travel rate of the travel mechanism and the extrusion rate of the stirring mechanism.

[0063] Furthermore, the comprehensive score E of the printing effect is:

[0064] E=50%×H+25%×S+25%×C,

[0065] in,

[0066] In the formula, H is the height completion rate, H = h a / h0,h a is the actual printing height, h0 is the model preset height; F is the incidence of complete breakage of strips longer than 1 mm, N f is the number of layers where fracture occurs, N t is the total number of layers; V is the void distribution rate on the strip surface, A v is the gap area, A t is the total surface area; S is the strip surface integrity, C is the width excess rate, C0 is the number of measurement points where the width exceeds 120% of the preset width, and C tis the total number of measuring points; the implementation method of the width overrun rate C uses an edge detection algorithm (such as Canny edge detection) to identify the edge of the strip, selects a pair of symmetrical measuring points at equal intervals (such as every 5mm, 10mm) along the length direction of the strip, calculates the distance between the two edges as the width at each pair of measuring points, compares the width of each measuring point with the preset width, and calculates the overrun rate by counting the number of overrun points and the total number of measuring points;

[0067] The printing effect scoring result is 0-100%; when the score is ≥90%, it indicates that the material can be printed directly; when the score is <90%, it indicates that the material cannot be printed directly and needs to be optimized by adding additives through feedback of torque data.

[0068] Furthermore, different optimization methods can be selected according to different concrete material components. For example, for water-binder ratio, the printing result optimization can be based on the Bingham fluid model to analyze the yield stress and plastic viscosity of the material; for aggregate, the fineness modulus can be adjusted according to the aggregate grading theory; for fly ash, it can be adjusted according to the volcanic ash activity theory; for nano-modified materials, it can be adjusted based on the nano-material dispersion theory. It is also possible to optimize the concrete formula in the direction of good printing effect based on similar concrete formulas with good printing effect in the database.

[0069] Furthermore, it is a small stirring device or rheometer with a built-in torque-speed sensor. Figure 1-Figure 2 , Figure 8-Figure 9 These are the shear result diagrams of the ZD-50 stirring device and the rheometer of the small simulation unit. From the comparison of the figures, it can be seen that the biggest difference between the simulator and the rheometer test is the numerical magnitude - the dynamic / static torque growth rate measured by the simulator is about 2-10 times that of the rheometer. Under static conditions, the rheometer test shows that the best number of layers can be obtained when the torque growth rate is 3.0-3.5N·m / s and the yield torque is 4.5-5.0N·m; corresponding to the ZD-50 stirring device, the optimal area appears at a static torque growth rate of 20-25N·m / s and a static yield torque of 8-10N·m. Under dynamic conditions, the rheometer test shows that the optimal range is within the range of torque growth rate 0.4-0.6N·m / s (r / s) and yield torque 0.8-1.0Mm, while for the ZD-50 stirring device, the optimal area under dynamic conditions appears at a torque growth rate of 15-20Nm / (r / s) and a yield torque of about 2-3Nm. Both tests show that the optimal parameters under dynamic conditions decrease, which indicates that this nonlinear characteristic is a property of the material itself, not caused by the test method. Considering that the simulator is closer to the actual 3D concrete printing, a small mixing device such as the ZD-50 mixer is preferred as a small simulation unit, but a rheometer can be used for quick screening.

[0070] Next, the method of the present invention is described with a specific example. The database has been preliminarily established based on the previous experimental results, so it is not shown in the following steps; at the same time, in order to illustrate the reliability of the evaluation results of the present invention, printing is performed through an actual printing unit and the printing effect is evaluated.

[0071] A method for quickly evaluating the printability of 3D printed concrete based on torque feedback, the specific implementation steps are as follows:

[0072] A cement-based 3D printing material with a water-binder ratio of 0.30 and a mineral admixture replacement rate of 30% was selected for a rapid evaluation of its printability.

[0073] (1) Equipment preparation and basic configuration

[0074] The actual printing unit uses ZD-300 3D printing equipment, including The main mechanism and travel mechanism of the mixing barrel are equipped with a first sensor, which can be a KH-T8 torque sensor; the small simulation unit adopts a ZD-50 stirring device, the mixing barrel capacity is 50L, and is equipped with a second sensor, which can be a KH-T5 torque-speed sensor; the effect detection unit adopts a high-speed camera system with a frame rate of 1000fps, equipped with an automatic image analysis program, which is used to evaluate the printing results of the actual printing unit.

[0075] (2) Basic testing and data collection

[0076] The concrete material to be tested was loaded into the actual printing unit and the small simulation unit at the same time. The actual printing unit was set with an initial travel speed of 60 mm / s and an extrusion rate of 0.6 r / s; the small simulation unit was set with a stirring speed of 0.6 r / s.

[0077] First, a low-speed constant shear test was performed with the rotation speed set to 0.025 r / s. The static yield torque was recorded to be 3.2 N·m and the torque-time growth rate was 22.5 N·m / s. Subsequently, a high-speed to low-speed shear test was performed, and the dynamic yield torque was recorded to be 2.6 N·m and the torque-speed growth rate was 17.8 N·m / (r / s). Figure 5 and Figure 6 The schematic diagram of obtaining the static and dynamic yield torque growth rates is shown. Figure 5 , Figure 6 The slope of the fitted straight line in the scatter plot is the static and dynamic yield torque growth rate.

[0078] (3) Printing effect evaluation

[0079] Print evaluation using standard test models, including cylinders and single-layer wall (20×500mm2). The effect detection unit records the following parameters:

[0080] The actual printing height is 285mm, the preset height is 300mm, and the calculated height completion rate H = 95%;

[0081] The strip surface void distribution rate V = 3%, the fracture occurrence rate F = 2%, and the surface integrity S = 95%;

[0082] The total number of width measurement points is 200, the number of over-limit points is 16, and the calculated width over-limit rate C = 8%;

[0083] According to the comprehensive scoring formula of printing effect E=50%H+25%S+25%C, the comprehensive score is calculated to be 94.5%.

[0084] (4) Parameter optimization and solution determination

[0085] Based on the database comparison, the torque characteristics of the material fall into the optimal printing range (static torque growth rate 20-25N·m / s, dynamic torque growth rate 15-20N·m / (r / s), and no ratio adjustment is required. Through three sets of printing parameter tests, the optimal printing parameters were finally determined: travel rate 65mm / s, extrusion rate 0.65r / s.

[0086] (5) Verification test

[0087] The optimized printing parameters were used for verification printing, and 5 groups of standard test pieces were printed continuously. The height completion rate reached more than 98%, the surface integrity remained above 96%, the width excess rate was controlled within 5%, and the comprehensive score was stable at more than 95%, proving that the material has good printability and the printing parameters are set reasonably.

[0088] (6) Database update

[0089] The torque-speed curve, rheological parameters, printing effect score and optimal printing parameters obtained from this test are entered into the database for reference in the subsequent rapid evaluation of similar materials.

[0090] The present invention uses a rapid evaluation method of torque feedback to complete material printability evaluation and printing parameter optimization in only about 0.5 hours. Compared with the traditional rheometer test method, the efficiency is increased by about 70%, and the printing effect is reliably guaranteed.

[0091] Next, the evaluation, verification and optimization process of 3D printing concrete of 7 examples with different formulations are given. Among them, Examples 1-6 were optimized once or twice, and finally more than 80% of concrete materials with good printability were obtained; Example 7 is a printing concrete designed according to the optimal interval parameters obtained in the previous study, which directly has good printability.

[0092] Example 1

[0093] A method for quickly evaluating the printability of 3D printed concrete based on torque feedback, the specific steps are as follows.

[0094] 3D printing concrete with a water-cement ratio of 0.42 and a mineral admixture replacement rate of 15% was selected for evaluation. Initial tests showed that the static yield torque was 1.8N·m, the torque-time growth rate was 12.3N·m / s; the dynamic yield torque was 1.2N·m, and the torque-speed growth rate was 8.5N·m / (r / s). These parameters are significantly lower than the requirements of the printable range (static torque growth rate 20-25N·m / s, dynamic torque growth rate 15-20N·m / (r / s)), indicating that the material has excessive fluidity due to the high water-cement ratio and lacks sufficient supporting strength, and the raw material ratio should be adjusted.

[0095] Printing effect verification: The actual printing height only reached 195mm (preset 300mm), and the height completion rate H was calculated to be 65%; the strip surface showed 8% void rate and 6% fracture rate, and the surface integrity S was 72%; at the same time, the width overrun rate C was measured to be 28%, reflecting the poor self-sustaining property of the material. According to the comprehensive scoring formula of printing effect E = 50% H + 25% S + 25% C, the comprehensive score was only 67.5%, indicating that the material does not meet the requirements of 3D printing under the existing ratio.

[0096] Based on the analysis of the Bingham fluid model, in order to improve the yield stress and plastic viscosity of the material, the cohesion of the slurry is first enhanced by reducing the water-binder ratio to 0.38. At the same time, in order to maintain appropriate fluidity, 0.3% of the water reducer is added. The reduction of the water-binder ratio can directly increase the static yield strength, while the addition of the water reducer can regulate the dynamic rheological properties, so that the material has good pumpability while maintaining sufficient support strength.

[0097] The optimized test results show that the static yield torque is increased to 2.8N·m, and the torque-time growth rate reaches 19.5N·m / s; the dynamic yield torque is increased to 2.2N·m, and the torque-speed growth rate reaches 16.8N·m / (r / s). These parameters are close to the optimal printing range, and the printing effect is significantly improved: the height completion rate is increased to 92%, the surface integrity is increased to 85%, and the width overrun rate is reduced to 15%. According to the same scoring equation, the comprehensive score of the material is increased to 86%, reaching the standard for optimized use.

[0098] Example 2

[0099] 3D printing concrete with a water-cement ratio of 0.32 and a mineral admixture replacement rate of 45% was selected for evaluation. Initial tests showed that the static yield torque was 4.5N·m, the torque-time growth rate was 28.6N·m / s; the dynamic yield torque was 3.8N·m, and the torque-speed growth rate was 22.4N·m / (r / s). These parameters all exceeded the upper limit of the optimal range (static torque growth rate 20-25N·m / s, dynamic torque growth rate 15-20N·m / (r / s)), indicating that the material viscosity is too high and the fluidity is insufficient, and the raw material ratio should be adjusted.

[0100] This judgment was verified during the printing process: the material had obvious resistance during extrusion, resulting in an actual printing height of only 135mm (preset 300mm), and the height completion rate was calculated to be H = 45%; the strip surface had a void rate of 15% and a break rate of 12%, and the surface integrity was S = 65%; at the same time, the width overrun rate was measured to be C = 35%. According to the comprehensive scoring formula for printing effect E = 50% H + 25% S + 25% C, the comprehensive score was only 55%, indicating that the material is completely unsuitable for 3D printing in its current state.

[0101] Based on the Bingham fluid model, in order to reduce the yield stress and plastic viscosity of the material, the water-binder ratio was first increased to 0.35, and 0.2% water reducer was introduced. This adjustment plan is based on the following considerations: Properly increasing the water-binder ratio can reduce the static yield strength, and the introduction of water reducer can improve the fluidity of the material, but the amount needs to be controlled to avoid excessively reducing the supporting capacity of the material.

[0102] The test results after the first optimization showed that the static yield torque dropped to 3.5N·m, the torque-time growth rate dropped to 23.2N·m / s; the dynamic yield torque dropped to 2.8N·m, and the torque-speed growth rate dropped to 19.5N·m / (r / s). The printing effect improved: the height completion rate increased to 78%, the surface integrity increased to 75%, and the width overrun rate decreased to 25%. The comprehensive score increased to 75%, but it still did not reach the optimal standard.

[0103] In order to further optimize the material performance, the amount of water reducer was adjusted to 0.8%. This adjustment was based on the first optimization results showing that the material still had room for optimization, and the torque parameters showed that the printing performance could be optimized by further improving the fluidity. The final test results showed: static yield torque 3.1N·m, torque-time growth rate 21.5N·m / s; dynamic yield torque 2.5N·m, torque-speed growth rate 17.2N·m / (r / s). These parameters all fell into the optimal printing range, and the printing effect was significantly improved: the height completion rate reached 90%, the surface integrity increased to 83%, and the width overrun rate was reduced to 18%. The final comprehensive score reached 85%.

[0104] Example 3

[0105] 3D printed concrete with a water-cement ratio of 0.38, a mineral admixture replacement rate of 25%, and fine sand with a fineness modulus of 1.8 as aggregate was selected for evaluation. Initial tests showed that the static yield torque was 2.2N·m, the torque-time growth rate was 15.6N·m / s; the dynamic yield torque was 1.5N·m, and the torque-speed growth rate was 11.2N·m / (r / s). These parameters are lower than the lower limit of the optimal range (static torque growth rate 20-25N·m / s, dynamic torque growth rate 15-20N·m / (r / s)), and compared with concrete with normal graded sand, its static conformability is obviously insufficient, and the raw material ratio should be adjusted.

[0106] Printing effect verification: In the printing test, the material showed poor interlayer bonding and large deformation: the actual printing height was 174mm (preset 300mm), and the calculated height completion rate H = 58%; due to unreasonable aggregate grading, the surface void rate was 12% and the fracture rate was 8%, and the surface integrity S was only 68%; the width overrun rate C reached 32%. According to the comprehensive scoring formula of printing effect E = 50% H + 25% S + 25% C, the comprehensive score was 62%, indicating that the material performance needs to be improved urgently.

[0107] Based on the aggregate grading theory, the fineness modulus of the sand is first adjusted to 2.3 to optimize the void ratio between aggregates, and 0.5% thickener is added to increase the viscosity of the slurry. Increasing the fineness modulus of the sand can improve the aggregate grading and optimize the internal structure of hardened concrete; while the addition of thickener can increase the plastic viscosity and yield stress of the slurry and enhance the material's ability to retain its shape.

[0108] The test results after the first optimization showed that the static yield torque increased to 2.6N·m, and the torque-time growth rate increased to 18.8N·m / s; the dynamic yield torque increased to 2.0N·m, and the torque-speed growth rate increased to 15.5N·m / (r / s). The printing effect was significantly improved: the height completion rate increased to 82%, the surface integrity increased to 78%, and the width overrun rate decreased to 22%. The comprehensive score increased to 78%, but there is still a gap from the optimal printing range.

[0109] To further optimize the material properties, the water-to-binder ratio was adjusted to 0.36, and the amount of glue was increased by 5%. This adjustment was based on the torque curve analysis after the first optimization, and the static conformability of the material still had room for improvement. The final test results showed: static yield torque 2.9N·m, torque-time growth rate 20.8N·m / s; dynamic yield torque 2.4N·m, torque-speed growth rate 16.8N·m / (r / s). The material performance was significantly improved: the height completion rate reached 90%, the surface integrity increased to 85%, and the width overrun rate was reduced to 15%. The final comprehensive score reached 85%.

[0110] Example 4

[0111] A 3D printing concrete with high fly ash content (replacement rate 50%) and water-binder ratio of 0.36 was selected for evaluation. Initial tests showed that the static yield torque was 2.1N·m, the torque-time growth rate was 13.2N·m / s; the dynamic yield torque was 1.4N·m, and the torque-speed growth rate was 9.8N·m / (r / s). These parameters are all lower than the optimal range (static torque growth rate 20-25N·m / s, dynamic torque growth rate 15-20N·m / (r / s)), and the ratio of dynamic and static parameters is significantly low, indicating that the material has slow early strength development due to high fly ash substitution, and the raw material ratio should be adjusted.

[0112] Printing effect verification: obvious interlayer deformation occurred in the printing test; the actual printing height was 156mm (preset 300mm), and the height completion rate H was calculated to be 52%; although the surface void rate was only 6% and the fracture rate was 7%, the surface integrity S was 75%, but the width overrun rate C was as high as 38%, reflecting the insufficient support performance of the material. According to the comprehensive scoring formula of printing effect E = 50% H + 25% S + 25% C, the comprehensive score was 61.8%.

[0113] Based on the theory of volcanic ash activity, 5% silica fume is first added to supplement the early strength. Silica fume has a large specific surface area and high activity, and can quickly react with Ca(OH)2 to form CSH gel, making up for the slow early hydration reaction of fly ash. At the same time, the ultrafine filling effect of silica fume also helps to increase the viscosity of the slurry.

[0114] After the first optimization, the test results showed that the static yield torque increased to 2.4N·m, the torque-time growth rate increased to 16.5N·m / s; the dynamic yield torque increased to 1.8N·m, and the torque-speed growth rate increased to 13.2N·m / (r / s). The printing effect improved: the height completion rate increased to 76%, the surface integrity increased to 80%, and the width overrun rate decreased to 28%. The comprehensive material score increased to 73%, but further optimization is still needed.

[0115] In order to achieve better printing effects, a compound system of accelerator (0.8% by mass of cementitious material) and water reducer (1.2%) was introduced. This adjustment is based on the first optimization result. The early skeleton structure is quickly formed by the accelerator, and the fluidity is regulated by the water reducer. The final test results show: static yield torque 2.8N·m, torque-time growth rate 19.8N·m / s; dynamic yield torque 2.3N·m, torque-speed growth rate 16.5N·m / (r / s). The printing performance is significantly improved: the height completion rate reaches 88%, the surface integrity is maintained at 82%, and the width overrun rate is reduced to 16%. The final comprehensive score reached 83%.

[0116] Example 5

[0117] A 3D printing concrete modified with nano-silica (2% admixture) and a water-binder ratio of 0.34 was selected for evaluation. Initial tests showed that due to the high specific surface area characteristics of nanomaterials, the material requires a large amount of water and has poor dispersibility, resulting in significant fluctuations in torque data: static yield torque fluctuates in the range of 3.8-5.2N·m, and the torque-time growth rate varies between 25.5-32.1N·m / s; dynamic yield torque fluctuates in the range of 3.2-4.1N·m, and the torque-speed growth rate varies between 20.8-24.5N·m / (r / s). These unstable parameters are seriously beyond the optimal range (static torque growth rate 20-25N·m / s, dynamic torque growth rate 15-20N·m / (r / s)), and the raw material ratio should be adjusted.

[0118] Printing effect verification: There was an obvious "intermittent discharge" phenomenon during the printing process; the actual printing height was only 144mm (preset 300mm), and the height completion rate H was calculated to be 48%; the strip surface void rate was 18%, the breakage rate was 15%, and the surface integrity S was only 58%; the width overrun rate C reached 45%. According to the printing effect comprehensive scoring formula E = 50% H + 25% S + 25% C, the comprehensive score was only 49.8%.

[0119] Based on the theory of nanomaterial dispersion, the dispersibility of nano-silica was first improved by increasing the amount of polycarboxylate water-reducing agent to 1.5% and introducing 0.3% dispersant. This adjustment plan was based on the following considerations: the steric hindrance effect of polycarboxylate water-reducing agent can effectively disperse the gelling material, while the introduction of a special dispersant can further improve the dispersion stability of nanoparticles, thereby enabling the material to obtain stable rheological properties.

[0120] After the first optimization, the rheological properties of the material tended to be stable: the static yield torque was stable at 3.3N·m, and the torque-time growth rate dropped to 22.8N·m / s; the dynamic yield torque was stable at 2.7N·m, and the torque-speed growth rate dropped to 18.5N·m / (r / s). The printing effect was significantly improved: the height completion rate increased to 78%, the surface integrity increased to 70%, and the width overrun rate decreased to 25%. The comprehensive material score increased to 72%, but there is still a gap from the optimal printing range.

[0121] Further optimization was achieved by adjusting the water-cement ratio to 0.36 and using a compound admixture system (water reducer 1.5% + dispersant 0.3% + stabilizer 0.2%). This adjustment was based on the first optimization result. On the basis of ensuring dispersibility, water separation and segregation were controlled by introducing stabilizers. The final test results showed: static yield torque 3.0N·m, torque-time growth rate 21.2N·m / s; dynamic yield torque 2.4N·m, torque-speed growth rate 17.1N·m / (r / s). Printing performance was significantly improved: the height completion rate reached 92%, the surface integrity increased to 85%, and the width overrun rate was reduced to 14%. The final comprehensive score reached 87%.

[0122] Example 6

[0123] A 3D printing concrete using recycled concrete aggregate (replacement rate 40%) and water-cement ratio of 0.37 was selected for evaluation. Initial tests showed that due to the high water absorption characteristics of recycled aggregate, the workability of the material decayed rapidly: the static yield torque increased rapidly from the initial 2.5N·m to 4.2N·m, and the torque-time growth rate increased from 16.8N·m / s to 27.5N·m / s; the dynamic yield torque increased from 1.8N·m to 3.5N·m, and the torque-speed growth rate increased from 12.5N·m / (r / s) to 21.8N·m / (r / s). This significant time-varying characteristic causes the parameters to deviate rapidly from the optimal range (static torque growth rate 20-25N·m / s, dynamic torque growth rate 15-20N·m / (r / s)), and the raw material ratio should be adjusted.

[0124] Printing effect verification: The material consistency changes greatly during the printing process. The actual printing height is 165mm (preset 300mm), and the height completion rate H is calculated to be 55%; the strip surface void rate is 14%, the break rate is 11%, the surface integrity S is 63%; the width overrun rate C is 36%. According to the printing effect comprehensive scoring formula E = 50% H + 25% S + 25% C, the comprehensive score is only 59.5%.

[0125] Based on the characteristics of recycled aggregate and its influence on the rheological properties of concrete, the two-stage mixing method is first used, and the recycled aggregate is pre-wetted and surface treated. Pre-wetting can reduce the water absorption rate of recycled aggregate, and surface treatment can improve the interface characteristics of aggregate; the two-stage mixing method helps to fully wet the aggregate surface and slow down the loss of workability caused by aggregate water absorption.

[0126] After the first optimization, the rheological properties of the material tended to be stable: the static yield torque was stable at 2.8N·m, and the torque-time growth rate was 19.2N·m / s; the dynamic yield torque was stable at 2.2N·m, and the torque-speed growth rate was 15.8N·m / (r / s). The printing effect was significantly improved: the height completion rate increased to 80%, the surface integrity increased to 75%, and the width overrun rate decreased to 22%. The comprehensive material score increased to 76%, but the duration of workability still needs to be improved.

[0127] To further improve the printing performance, 0.6% of slump retaining agent was added to control the attenuation of workability, and the amount of adhesive was appropriately increased by 8% to compensate for the water absorption of recycled aggregate. This adjustment is based on the first optimization result. Chemical admixtures are used to delay the loss of workability while ensuring sufficient adhesive to meet the needs of recycled aggregate. The final test results show: static yield torque 2.9N·m, torque-time growth rate 20.5N·m / s; dynamic yield torque 2.3N·m, torque-speed growth rate 16.8N·m / (r / s). The printing performance has been significantly improved: the height completion rate reached 89%, the surface integrity increased to 83%, and the width overrun rate was reduced to 15%. The final comprehensive score reached 84%.

[0128] Example 7

[0129] A composite cementitious material system (cement: mineral powder: fly ash = 6:2:2) and a water-cement ratio of 0.35 for 3D printing concrete were selected for evaluation. The mix design was based on the optimal interval parameters obtained in previous studies, and continuously graded machine-made sand (fineness modulus 2.5) was used as aggregate. Initial tests showed: static yield torque 3.0N·m, torque-time growth rate 22.5N·m / s; dynamic yield torque 2.4N·m, torque-speed growth rate 16.8N·m / (r / s). These parameters all fall into the optimal range (static torque growth rate 20-25N·m / s, dynamic torque growth rate 15-20N·m / (r / s)), indicating that the material has a good balance of rheological properties and can be directly used as a raw material for 3D concrete printing.

[0130] Printing effect verification: excellent performance was shown in the printing test; the actual printing height was 285mm (preset 300mm), and the height completion rate H was calculated to be 95%; the strip surface had only 3% voids and 2% fracture rate, and the surface integrity S reached 94%; the width overrun rate C was only 8%. According to the comprehensive scoring formula of printing effect E = 50% H + 25% S + 25% C, the comprehensive score reached 93.5%. The reasonable proportion of composite cementitious materials not only provides sufficient early strength, but also ensures appropriate rheological properties; the controlled water-binder ratio and the use of continuously graded aggregates provide the material with a stable internal structure; finally, by adding a compound system of 0.8% polycarboxylic acid water reducer and 0.2% thickener, a good balance of fluidity and cohesion is achieved.

[0131] To verify the stability of the ratio, an intermittent printing test lasting 4 hours was carried out. The fluctuation range of the torque parameter was controlled within 5%, the printing quality remained stable, and the comprehensive score was always maintained above 90%.

[0132] For those skilled in the art, without departing from the core spirit and basic principles of the present invention, they can freely make various adjustments and equivalent substitutions to the technical solutions. Therefore, all adjustments, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for quickly evaluating the printability of 3D printed concrete based on torque feedback, characterized in that: The following steps are involved: Step S1: Equipment preparation and basic configuration: An actual printing unit, a small simulation unit, and an effect detection unit are provided; the actual printing unit is a 3D printing device for carrying out actual 3D printing operations, and the stirring mechanism is built-in with a first sensor for real-time sensing and recording the torque generated by the motor during the stirring process of the 3D printing device; the small simulation unit has a stirring function and is built-in with a second sensor for recording the torque generated by the motor during the material stirring process; the effect detection unit is used to evaluate the printing result of the actual printing unit; Step S2: Basic testing and data collection: The actual printing unit and the small simulation unit simultaneously print and mix the same fresh concrete material, and record their respective torque-speed curves; Step S3: Printing effect evaluation: The standard test model is printed using the fresh concrete material, and the printing effect of the actual printing unit is scored using the effect detection unit; the corresponding relationship between the torque-speed curve and the printing effect of the actual printing unit and the small simulation unit is established; Step S4: Establishing a database and determining optimal parameters: Prepare concrete of various components, repeat steps S2 and S3, and construct a database of the torque-speed curve of the actual printing unit, the torque-speed curve of the small simulation unit, the printing effect, and the printing parameters of the actual printing unit; Based on the numerical comparison of the printing effect results in the database, the optimal printing range of the torque characteristic is determined according to the optimal printing effect range; the torque characteristic includes the static torque growth rate and the dynamic torque growth rate; Step S5: Printability evaluation of concrete material X: For concrete material X with unknown printing characteristics, a small simulation unit is used to obtain the torque characteristics of concrete material X to determine whether the torque characteristics of the unknown concrete material fall within the optimal printing range of the torque characteristics; if it falls within the optimal printing range of the torque characteristics, the concrete material X has good printability and no proportion adjustment is required.

2. The method for rapidly evaluating the printability of 3D printed concrete based on torque feedback according to claim 1, characterized in that: The method further includes step S6, determining printing parameters: for concrete materials whose torque characteristics fall within the optimal printing range of torque characteristics, multiple sets of printing parameter tests are performed by an actual printing unit, and the optimal printing parameters are selected according to the result values ​​of the printing effect; The printing parameters include a traveling speed of the traveling mechanism and an extrusion speed of the stirring mechanism.

3. The method for rapidly evaluating the printability of 3D printed concrete based on torque feedback according to claim 1, characterized in that: Step S5 also includes a database updating step: entering the torque-speed curve, rheological parameters, printing effect score and optimal printing parameters obtained by testing the concrete material X with unknown printing characteristics into the database.

4. The method for rapidly evaluating the printability of 3D printed concrete based on torque feedback according to claim 1, characterized in that: The comprehensive score E of printing effect is: E=50%×H+25%×S+25%×C, in, In the formula, H is the height completion rate, H = h a / h0,h a is the actual printing height, h0 is the model preset height; F is the incidence of complete breakage of strips longer than 1 mm, N f is the number of layers where fracture occurs, N t is the total number of layers; V is the void distribution rate on the strip surface, A v is the gap area, A t is the total surface area; S is the strip surface integrity, C is the width excess rate, C0 is the number of measurement points where the width exceeds 120% of the preset width, C t is the total number of measurement points; The printing effect scoring result is 0-100%; when the score is ≥90%, it indicates that the material can be directly printed; when the score is <90%, it indicates that the material cannot be directly printed.

5. The method for rapidly evaluating the printability of 3D printed concrete based on torque feedback according to claim 1, characterized in that: The optimal printing range of torque characteristics is the static torque growth rate of 20-25N·m / s and the dynamic torque growth rate of 15-20N·m / (r / s).

6. The method for rapidly evaluating the printability of 3D printed concrete based on torque feedback according to claim 1, characterized in that: The standard test model is a cylindrical model and a single-layer wall model. The cylindrical model has a single layer of 20×φ300mm. 2 ; Single-layer wall model single layer 20×500mm 2 ; The actual printing unit travel speed is 60mm / s, the extrusion rate is 0.6r / s; the small simulation unit rotation speed is 0.6r / s.

7. The method for rapidly evaluating the printability of 3D printed concrete based on torque feedback according to claim 1, characterized in that: Based on the Bingham model, the static yield torque in the small simulation unit and the growth rate of the torque reflecting the elastic modulus over time are obtained by setting the low-speed constant shear mode; the dynamic yield torque and the growth rate of the torque reflecting the material viscosity with the speed are obtained by setting the high-speed to low-speed shear mode; The corresponding relationship between the torque-speed curve and the printing effect is obtained through consistent testing of different concrete materials and recorded in the database.

8. The method for rapidly evaluating the printability of 3D printed concrete based on torque feedback according to claim 1, characterized in that: The small simulation unit is capable of performing rheological property tests based on the Bingham model; the shear force of the rheological property test procedure is applied using the small simulation unit to obtain the torque-time curve performance of the concrete material X corresponding to the unknown printing characteristics.

9. The method for rapidly evaluating the printability of 3D printed concrete based on torque feedback according to claim 1, characterized in that: The actual printing unit is a 3D printing device for carrying out actual 3D printing operations, and the actual printing unit includes a stirring mechanism and a traveling mechanism, wherein the stirring mechanism has the function of adjusting the nozzle traveling speed and the material extrusion speed during the printing process; the stirring mechanism is built-in with a first sensor for real-time sensing and recording the torque generated by the motor during the stirring process of the 3D printing device; the small simulation unit includes at least a second stirring mechanism, and the capacity of the second stirring mechanism is smaller than the capacity of the first stirring mechanism of the actual printing unit; the second stirring mechanism is built-in with a second sensor for real-time sensing and recording the torque and speed generated by the motor during the stirring process; The effect detection unit is configured as a high-speed camera system with continuous recording and image recognition functions, which can continuously record the height of the 3D printed structure and the distribution and ratio characteristics of appearance defects when the actual printing unit is working; the effect detection unit has a built-in rapid analysis program system for evaluating the printing effect based on the height and completeness of the 3D printed structure.

10. The method for rapidly evaluating the printability of 3D printed concrete based on torque feedback according to claim 1, characterized in that: The small simulation unit is a small stirring device or a rheometer with a built-in torque-speed sensor.

Citation Information

Patent Citations

  • Online testing method for 3D printing dynamic characteristics of cement-based material

    CN110954442A

  • Device and method for testing extrudability and fresh-mixed state mechanical properties of 3D printed concrete

    CN111175184A

  • 3D printing engineering parameter matching method

    CN114442968A

  • 3D printing concrete with adjustable rheological property, preparation method and printing process

    CN114804791A

  • 3D concrete printing surface smoothness evaluation method

    CN118189862A

Cited By

  • Printing structure design and parameter optimization method based on process defect tolerance coefficient

    CN121340436A